Penta-Helix Collaboration in Renewable Energy Policy Governance: Evaluating the Role of Non-State Actors in Indonesia's Energy Self-Sufficient Village Program - Baan, Bram B (Inovasi Pratama Internasional. Ltd, 2025)
Indonesia's transition towards renewable energy requires comprehensive governance frameworks that engage multiple stakeholders beyond traditional government actors. This study examines the implementation of the penta-helix collaboration model in renewable energy policy governance, with specific focus on non-state actors' roles in the Energy Self-Sufficient Village (Desa Mandiri Energi/DME) program. Using a qualitative research methodology, this investigation analyzes the collaborative dynamics between government, academia, business sector, community, and media in advancing renewable energy initiatives at the village level. The research reveals that non-state actors play crucial roles as policy entrepreneurs, implementers, and sustainability champions within the DME framework. However, challenges persist in coordination mechanisms, resource allocation, and institutional capacity building. The findings demonstrate that effective penta-helix collaboration requires structured governance frameworks, clear role definitions, and sustained political commitment to achieve meaningful renewable energy transformation at the grassroots level. This research contributes to the understanding of multi-stakeholder governance models in energy transition contexts and provides insights for policymakers seeking to enhance collaborative approaches in renewable energy development.